Breast cancer: analysis from transdisciplinary, psychosocial and gender perspectives in Chile and Catalonia - Rodríguez, Pía; Pino, Juan; March, Marian (Revista Chilena de Salud Pública, 2019)
Background: Breast cancer is the leading cause of cancer death in women worldwide. Our objective was to compare the public health policies of breast cancer in Chile and Catalonia, under transdisciplinary, psychosocial and gender perspectives. Material and Methods: Qualitative descriptive study, which used the method of comparative analysis to compare public policies on breast cancer in Chile and Catalonia between 2005 and 2016. Results: The transdisciplinary perspective was not considered, with both regions only taking a multidisciplinary approach. For its part, the psychosocial perspective was described as relevant in the disease cycle, but in practice both sites showed limited application of this perspective. With respect to the gender perspective, Chile has incorporated it into strategies, though not consistently manner, while Catalonia mentions small elements, without being explicit about the approach. The identified emergent categories include a political/epidemiological perspective, with both locations prioritizing the development and execution of public policies to address the pathology, as well as a perspective of user empowerment, which both Chile and Catalonia identify as a fundamental aspect of medical decision making. Conclusions: The analyzed perspectives are in early stages of development; however, they are not yet in line with social demands nor current health epistemology. In terms of the comparison, there are greater similarities than differences between the two sites, and both are just starting to articulate the analyzed approaches. For now, it is important that both sites start transforming their understanding of breast cancer, and a pending task will be to materialize that new approach into health protocols and guides.